Educative Game Tool (Ape) "Dadu Putar Huruf" For Early Children in Miftahul Khoeriyah Paud In Bungursari Sub-District - Anugerah, Dandi; Yahya, Muhammad Ilham; Annur M, Ade Isna; H, Yunita Sri; Nizar P, Ajeng; Novitasari, Aliffiah; Nurazizah, Dina; Anggita, Sahira; Salsabila, Nabila; Rizal, Fahrul; Maruf, Cipta Muhammad; Alysa F, Ayunda; Nurul Istiqomah, Insya Siti; Rissa Nuryuniarti (AbdimasMu UMTAS, 2023)
The success of implementing an educational program for early childhood depends on the management of learning resources, one of which is the Educational Game Tool (APE). Educational Game Tools (APE) are everything that can be used as a means or equipment to play that contains educational value (education) and can develop all children's abilities. APE aims as a means to assist teachers in developing competence for the growth and development of students. The benefits of APE itself are as a learning aid for children, especially for early childhood, so that children are not bored and excited in participating in learning activities. APE is also able to develop the 6 aspects of development, namely religion and morals, physical motoric, cognitive, language, socio-emotional, and children's art. One of the APEs is in the form of “Dadu Putar Huruf” The Dice Rotating Letters made or designed are expected to help the learning process in developing competence for growth and development of early childhood